Hydrodynamics and masstransfer process of rectification in a centrifugal vehicle - Серябряков, Богдан Андрійович (Technology audit and production reserves, 2012)
The article described and justified by theoretical and experimental study of hydrodynamics and mass transfer in a gas-liquid by centrifugal force, process modeling, development of methods of engineering calculation of highly energy-and resource-saving equipment